Insights into the Evolutionary History of the Hawaiian Bidens (Asteraceae) Adaptive Radiation Revealed Through Phylogenomics. (18th January 2020) - Knope, Matthew L; Bellinger, M Renee; Datlof, Erin M; Gallaher, Timothy J; Johnson, Melissa A
Abstract: Hawaiian plant radiations often result in lineages with exceptionally high species richness and extreme morphological and ecological differentiation. However, they typically display low levels of genetic variation, hindering the use of classic DNA markers to resolve their evolutionary histories. Here we utilize a phylogenomic approach to generate the first generally well-resolved phylogenetic hypothesis for the evolution of the Hawaiian Bidens (Asteraceae) adaptive radiation, including refined initial colonization and divergence time estimates. We sequenced the chloroplast genome (plastome) and nuclear ribosomal complex for 18 of the 19 endemic species of Hawaiian Bidens and 4 outgroup species. Phylogenomic analyses based on the concatenated dataset (plastome and nuclear) resulted in identical Bayesian and Maximum Likelihood trees with high statistical support at most nodes. Estimates from dating analyses were similar across datasets, with the crown group emerging 1.76–1.82 Mya. Biogeographic analyses based on the nuclear and concatenated datasets indicated that colonization within the Hawaiian Islands generally followed the progression rule with 67–80% of colonization events from older to younger islands, while only 53% of events followed the progression rule in the plastome analysis. We find strong evidence for nuclear-plastome conflict indicating a potentially important role for hybridization in the evolution of the group. However, incomplete lineage sorting cannot be ruled out due to the small number of independent loci analyzed. This study contributes new insights into species relationships and the biogeographic history of the explosive Hawaiian Bidens adaptive radiation.